Towards a theory-based assessment of the Climate Smart Agriculture Strategy (EASAC) for the SICA Region - Collazos, Sara; Howland, Fanny C.; Le Coq, Jean-François (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The EASAC Theory of Change aiming at scaling climate-smart agriculture in the SICA region is made up of 4 main routes to achieve the desired impact: 1 policy route, 1 institutional route, 1 financing route, and 1 communication route. Since the EASAC launch in 2017, a total of 259 changes were identified by key informants: 226 at the country level and 33 at the regional level. Most of the changes are concentrated in the policy route, followed by the institutional route. The financial route is mainly strengthened through international cooperation actors.Guatemala and Costa Rica are the countries with the most changes identified by key informants.